The uses and impact of social and emerging media on public relations practices in Malaysia - Lee, Cheng Ean Catherine *; Ong, May Kay *; Lim, Siz Siz; Chuan, Tek Pheung (University of Newcastle, Australia, 2020)
Research has shown that social media has been widely discussed among public relations practitioners and scholars in relation to how it has changed public relations practices. A study by Wright and Hinson (2017) revealed that public relations practitioners continue to strongly agree that social and other emerging media technologies have brought dramatic changes to how public relations is practiced in the United States of America. In the Malaysian context, the explosion in social media, especially social networking site such as Facebook, has caused many public relations practitioners to recognise the need to embrace these new media for effective communication with the internal and external audiences. Drawing on Wright and Hinson’s (2016) survey instrument, this study measured the actual use of social and other emerging media by public relations practitioners in Malaysia, and explored its impact on public relations practices. Through a web-based survey, this study found evidence that public relations practitioners in Malaysia have frequently used social media especially Facebook, Instagram and LinkedIn. On average, they spent approximately 26% to 50% of their working time using social and emerging media for public relations and communications activities. The results of this study provide useful insights for academics, researchers and public relations practitioners on how social and emerging media technologies are used in the Malaysian public relations industry.